2009
DOI: 10.1093/ilar.50.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Assessing Fish Welfare

Abstract: Descriptions of feeling states in nonhuman animals have relied on indirect evidence from empirical data. Assumptions that fish do not experience suffering lack evidence and in fact contradict a large body of indirect scientific evidence and ethical concern. Why should the burden of proof rest on those defending the hypothesis that fish feel pain and other discomfort? In this article I address this controversy and describe typical methodsand the problems associated with themto identify animal welfare (feeling-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 84 publications
1
37
0
Order By: Relevance
“…Indeed, we would generally consider that where caging is involved, and in particular where exotic forms are concerned that require highly specialised temperature and humidity care, most if not all of these animals fit into the 'difficult' or 'extreme' categories. Numerous authors have concluded that captive conditions frequently result in stress, morbidity and premature mortality, for example, invertebrates (Smith 1991;Elwood 2011;Crook 2013), fishes (Wabnitz et al 2003;Livengood and Chapman 2007;Volpato 2009); Meijboom and Bovenkerk 2013), amphibians (DPI 2006;Arena et al 2012), reptiles (Warwick 1995;Kreger 2002;Toland et al 2012;Warwick et al 2013), birds (Mather 2001;Engebretson 2006;Meehan and Mench 2008;van Zeeland et al 2009), and mammals (Hediger 1955;Hutchins et al 1984;Broom and Johnson 1993;Morgan and Tromberg 2007;Soulsby et al 2009). In summary, there is a risk that current practices may fail to cater for all of the five freedom requirements.…”
Section: Welfarementioning
confidence: 99%
“…Indeed, we would generally consider that where caging is involved, and in particular where exotic forms are concerned that require highly specialised temperature and humidity care, most if not all of these animals fit into the 'difficult' or 'extreme' categories. Numerous authors have concluded that captive conditions frequently result in stress, morbidity and premature mortality, for example, invertebrates (Smith 1991;Elwood 2011;Crook 2013), fishes (Wabnitz et al 2003;Livengood and Chapman 2007;Volpato 2009); Meijboom and Bovenkerk 2013), amphibians (DPI 2006;Arena et al 2012), reptiles (Warwick 1995;Kreger 2002;Toland et al 2012;Warwick et al 2013), birds (Mather 2001;Engebretson 2006;Meehan and Mench 2008;van Zeeland et al 2009), and mammals (Hediger 1955;Hutchins et al 1984;Broom and Johnson 1993;Morgan and Tromberg 2007;Soulsby et al 2009). In summary, there is a risk that current practices may fail to cater for all of the five freedom requirements.…”
Section: Welfarementioning
confidence: 99%
“…This approach has essentially been defined in terrestrial farm animals within the ''five freedoms'' discussed previously. An extension of the feelings-based approach to aquatic animal welfare has been proposed in which it is suggested that welfare needs should be guided by the wants and preferences of the aquatic animal (Volpato et al 2007;Volpato 2009). Huntingford et al (2006) acknowledged that several definitions of animal welfare exist, and also acknowledged that wild fish naturally experience a variety of adverse conditions, from attack by predators or conspecifics to starvation, or exposure to poor environmental conditions.…”
Section: The ''Five Freedoms'' Approachmentioning
confidence: 99%
“…They then stated this does not make it acceptable for humans to impose such conditions on fish (Huntingford et al 2006), even though anthropogenic impacts on natural aquatic ecosystems have unavoidably resulted in exposure of wild fish to poor environmental conditions throughout the developed world (discussed in more detail below). Animal rights and animal liberation derivations of the feelingsbased approach to welfare also exist (Arlinghaus et al 2007a, which if left to their logical conclusion, ultimately lead some authors to reject the legitimacy of historically acceptable activities such as aquarium keeping and fishing (Volpato 2009). …”
Section: The ''Five Freedoms'' Approachmentioning
confidence: 99%
See 2 more Smart Citations